557. AN EXPERIENCE OF LAPAROSCOPIC GASTRECTOMY AND FUNDOPLICATION FOR A PATIENT WITH NEUROENDOCRINE TUMOR AND LARGE HIATAL HERNIA WITH UPSIDE-DOWN STOMACH. (24th September 2022) - Kamiya, Satoshi; Furukawa, Kenichiro; Nagata, Masato; Koseki, Yusuke; Fujiya, Keiichi; Hikage, Makoto; Tanizawa, Yutaka; Terashima, Masanori; Bando, Etsuro
Abstract: The case of a neuroendocrine tumor arising from an upside-down stomach due to a large hiatal hernia is rare but occasionally encountered in clinical practice. As we experienced such a case and successfully treated by simultaneous laparoscopic distal gastrectomy and hernia repair with fundoplication, we here report our experience. A 79-year-old woman was referred to our hospital with suspicion of a stomach submucosal tumor. Detailed examination revealed the submucosal tumor in diameter of 20mm located on the middle third of stomach, and the pathology of biopsy showed the positivity for Chromogranin-A and Synaptophysin. CT scan also demonstrated the large hiatal hernia with prolapsing the almost whole stomach and transverse colon to the left thoracic cavity. We diagnosed that as Rindi classification type III neuroendocrine tumor and complex esophageal hiatal hernia, and we planned laparoscopic distal gastrectomy and hernia repair with fundoplication. Laparoscopy showed the prolapse of almost whole stomach and colon through the esophageal hilum to left thoracic cavity. We pull them back to abdominal cavity and divided the hernia sac at the level of hilum. After distal gastrectomy, we managed to close the enlarged esophageal hilum without using artificial mesh by suturing the crus of diaphragm. We added the Toupet fundoplication to remnant stomach, and reconstructed the digestive tract by means of Roux-en-Y method. There were no findings of passage obstruction or regurgitation in the peroral contrast examination. The patient was discharged 7 days after surgery with good postoperative course. Simultaneous laparoscopic gastrectomy and esophageal hiatus hernia repair was successfully performed. Enlarged esophageal hilum could be closed without using the artificial mesh even for the patient with an upside-down stomach, and Toupet fundoplication could be added for a small remnant stomach after distal gastrectomy. Therefore, our procedure was considered to be a safe and feasible minimally invasive surgery for such patients.